Graphene-based stretchable and transparent moisture barrier. (9th February 2018) - Won, Sejeong; Van Lam, Do; Lee, Jin Young; Jung, Hyun-June; Hur, Min; Kim, Kwang-Seop; Lee, Hak-Joo; Kim, Jae-Hyun
Abstract: We propose an alumina-deposited double-layer graphene (2LG) as a transparent, scalable, and stretchable barrier against moisture; this barrier is indispensable for foldable or stretchable organic displays and electronics. Both the barrier property and stretchability were significantly enhanced through the introduction of 2LG between alumina and a polymeric substrate. 2LG with negligible polymeric residues was coated on the polymeric substrate via a scalable dry transfer method in a roll-to-roll manner; an alumina layer was deposited on the graphene via atomic layer deposition. The effect of the graphene layer on crack generation in the alumina layer was systematically studied under external strain using an in situ micro-tensile tester, and correlations between the deformation-induced defects and water vapor transmission rate were quantitatively analyzed. The enhanced stretchability of alumina-deposited 2LG originated from the interlayer sliding between the graphene layers, which resulted in the crack density of the alumina layer being reduced under external strain.